العقود المالية المركبة وضوابطها: دراسة فقهية تحليلي = Complex financial contracts and disciplines: analytical jurisprudence study - Almushaifri, Yaqoob Ali Saleem; Muhamed, Sedrah Alshareef Mustafa; Abdul Aziz, Akhtarzaitie (IIUM Press, International Islamic University Malaysia, 2019)
لم يكن مصطلح "العقود المالية المركبة" في عهد الرسول ﷺ وصحابته رضوان الله عليهم، ولم يتعرض له الفقهاء قديمًا في مصادرهم مصطلحًا خاصًّا، وإنما تكلموا عن العقود المالية المجتمعة، وتهدف هذه الدراسة من خلال المنهج الوصفي إلى بيان حقيقة العقود المالية المركبة، وأقوال العلماء فيها، وتحليل هذه الأقوال والأدلة ومناقشتها، وتحديد القول الراجح في كل مسألة، وكيفية توظيف هذه العقود في المعاملات المالية المعاصرة، وقد خلصت الدراسة إلى أن العقود المالية المركبة مجموع العقود المالية المتعددة التي يشتمل عليها العقد الواحد، بحيث تُعدُّ جميع الحقوق والالتزامات المترتبة عليها بمنزلة آثار العقد الواحد، ولا يؤدي اجتماعها إلى عقد محرم، وأن الأصل في العقود المالية المركبة الإباحة إن ضُبطت بالضوابط التي اشترطها الفقهاء والمجامع الفقهية والهيئات الشرعية؛ إذا لم يكن التركيب بين العقدين محلَّ نهي شرعي، أو موصلاً إلى ما حرم الله تعالى، وأن يكون كل عقد صحيح بمفرده. ********************************************************************************* The term "composite financial contracts" did not exist during the era of the Prophet Muhammad (PBUH), nor in the era of the Sahaabah (RA). Moreover, Muslim jurists did not discuss this term in their texts as a special term; rather, they discussed the term "combined financial contracts." The purpose of this study, which uses a descriptive approach, is to illustrate the nature of the composite financial contracts and the Muslim scholars' opinions about it. The study also analyzes and discusses these opinions and their supportive evidence and highlights the most correct opinion for each related issue in this context and how to employ these contracts in the contemporary financial transactions. The study concluded that the composite financial contracts are a collection of multiple financial contracts that are included in a single contracts, so that all the rights and obligations resulting from this collection of contracts are considered the rights and obligations of a single contract, where the composite of these contract does not result in a prohibited contract. Principally, the composite financial contracts are permissible as long as they adhere to the conditions stipulated by the jurists, the jurisprudential councils, and Shariah bodies; where composing two or more contracts is not prohibited, not aimed at forbidden purposes, and every single contract, per se, is permissible.